MECHANICAL AND DURABILITY PROPERTIES OF WARM ASPHALT MIXTURE INVOLVING SYNTHETIC ZEOLITE - RASHED, ABDULLAH M.; AI, AL-HADIDY (Journal of Duhok University, 2023)
Warm mix asphalt (WMA) blends at temperatures lower than those in conventional mixtures by 20-50 °C. this study examines and contrasts the mechanical properties of hot mix asphalt (HMA) mixtures with those of WMA mixtures using synthetic zeolite (SZ) addition. 3.0%, 5.0%, and 7.0% of the total asphalt mass were added as additive to create the WMA mixes. The following tests were conducted: Marshall stability, indirect tensile strength at 25°C and 60°C, tensile stiffness modulus (TSM), deformation strength (DS), and semi-circular bending (SCB) tests. Tensile strength ratio (TSR) calculations were used to assess the combinations' durability performance and determine their susceptibility to moisture. The findings showed that WMA mixtures with 5% SZ achieved the minimal ASTM standards for stability, flow, voids in mineral aggregates, and TSR at the same optimum binder concentration. Besides, this mixture showed higher resistance to deformation and cracking than the control HMA. A SZ content of 5% by weight of asphalt is recommended for the production of the WMA mixtures similar to that investigated in this study